Perbedaan Prevalensi Karies Gigi dan Tingkat Keparahan Karies Gigi pada Anak Usia 3-5 Tahun Yang Ibunya Bekerja dan Tidak Bekerja : Kajian Pada PAUD Sapta Kemuning, Depok Jawa Barat (Laporan Penelitian) - Devita Rosalina; Jeddy Jeddy (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Dental caries is one of the problems that are often complained of by the people of Indonesia both in children and adults. The percentage of residents who have dental and mouth problems according to Riskesdas in 2007 and 2013 increased from 23.2% to 25.9%. In 2018 the Indonesian population who had dental and oral problems increased to 57.6%. The risk of caries is quite high in children aged 3 - 5 years, because at this age children usually like to eat food and drinks according to their wishes. Therefore, parents, especially mothers, have an important role in guiding their children so that they can maintain their teeth and mouth well and correctly.Objective: To find out whether there are differences in the prevalence of dental caries and the severity of dental caries in children whose mothers work and do not work Methods: This study was an observational analytic study with a cross sectional approach to know differences in caries prevalence and caries severity in 69 children aged 3-5 years whose mothers worked and did not work. The child is examined def-t by the supervisor, the parents are given a questionnaire containing 8 questions that has been tested for validity and reliability.Results : Caries severity was found in children whose mothers worked 4.9 (high) and in children whose mothers did not work 7.1 (very high). Caries prevalence in children whose mothers work is 78% and in children whose mothers do not work 95%. Conclusion: The results of data analysis showed that p > 0.05 (p = 0.23 and p = 0.08) which means that there was no difference in the prevalence of dental caries and the severity of dental caries in children whose mothers worked and did not work.